A novel precipitation-based synthesis for the formation of X8R-type dielectrics composition based on monodispersed submicron Ba0.991Bi0.006TiO3@Nb2O5 particles. Issue 9 (September 2015) - Liu, Yu; Cui, Bin; Wang, Yan; Zhao, Xiaotong; Yan, Qiangqiang; Wu, Tong; Zhao, Lili; Wang, Yaoyu
Abstract: To meet the needs of future multilayer ceramic capacitors (MLCCs), thinner dielectric layers are necessary. To achieve this goal, the grain size and uniformity of the MLCC particles must be effectively controlled. In this study, we developed a novel precipitation route to control the dispersion and particle size of Ba0.991 Bi0.006 TiO3 and Ba0.991 Bi0.006 TiO3 @Nb2 O5 particles. We confirmed a core–shell particle structure by means of X-ray diffraction, scanning electron microscopy, and energy-dispersive spectroscopy. The dielectric properties of the ceramics were measured using an LCR meter. We found monodispersed submicron Ba0.991 Bi0.006 TiO3 particles (∼233 nm) form a core that was coated with a homogeneous Nb2 O5 layer (∼7 nm). Dense, fine-grained Ba0.991 Bi0.006 TiO3 -based ceramics (≤250 nm) were obtained by sintering. The ceramics met the X8R requirements, with a Curie temperature of about 140 °C, a maximum dielectric constant of 2336, and a low dielectric loss at room temperature (<2.0%, with a minimum of 0.5%).